Testosterone reduces metabolic brown fat activity in male mice. Issue 1 (3rd September 2021) - Lantero Rodriguez, Marta; Schilperoort, Maaike; Johansson, Inger; Svedlund Eriksson, Elin; Palsdottir, Vilborg; Kroon, Jan; Henricsson, Marcus; Kooijman, Sander; Ericson, Mia; Borén, Jan; Ohlsson, Claes; Jansson, John-Olov; et al.
Abstract : Brown adipose tissue (BAT) burns substantial amounts of mainly lipids to produce heat. Some studies indicate that BAT activity and core body temperature are lower in males than females. Here we investigated the role of testosterone and its receptor (the androgen receptor; AR) in metabolic BAT activity in male mice. Castration, which renders mice testosterone deficient, slightly promoted the expression of thermogenic markers in BAT, decreased BAT lipid content, and increased basal lipolysis in isolated brown adipocytes. Further, castration increased the core body temperature. Triglyceride-derived fatty acid uptake, a proxy for metabolic BAT activity in vivo, was strongly increased in BAT from castrated mice (4.5-fold increase vs sham-castrated mice) and testosterone replacement reversed the castration-induced increase in metabolic BAT activity. BAT-specific AR deficiency did not mimic the castration effects in vivo and AR agonist treatment did not diminish the activity of cultured brown adipocytes in vitro, suggesting that androgens do not modulate BAT activity via a direct, AR-mediated pathway. In conclusion, testosterone is a negative regulator of metabolic BAT activity in male mice. Our findings provide new insight into the metabolic actions of testosterone.